Renewing the Thoughts of the Hijri Calendar of Muhammadiyah, Nahdlatul Ulama and Persatuan Islam and Its Implications for Realization of National Hijri Calendar - Marwadi, Marwadi (Fakultas Syariah IAIN Purwokerto, 2021)
This paper discusses the issue of renewing the thought of Hijri calendar by Muhammadiyah, Nahdlatul Ulama (NU) and Persatuan Islam and its implications for the existence of a national Hijri calendar. The focus of this paper is to highlight changes in methods and criteria, reference algorithms and the scope of the calendar application area. The main problem in this paper is how Muhammadiyah, NU and Persatuan Islam reform the Hijri calendar thoughts and what are the implications for the realization of the national Hijri calendar. The results of this study indicate that both Muhammadiyah, NU, and Persatuan Islam have updated the Hijri calendar's thought, both in the aspects of methods and criteria, algorithm references and the scope of the calendar application area, which leads to the conformity of the calendar concept that is normatively and scientifically appropriate. The renewal of thought is caused mass organizations face problems with the methods and criteria for determining the beginning of the month in the Hijri calendar. The renewal of thought also influenced by advances in science and technology. However, because this renewal has not been supported by the similar epistemology of determining the beginning of the month and the identity politics of mass organizations, the opportunity to realize a national Hijri calendar is still very unlikely.